PENGARUH LITERASI KEUANGAN, SELF-EFFICACY, KEMUDAHAN PENGGUNAAN PAYLATER TERHADAP KESEJAHTERAAN FINANSIAL (Studi pada Gen Z di DKI Jakarta) - Novi Yuliana Safitri; Hirdinis Hirdinis (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. This study aims to examine the influence of financial literacy, self-efficacy, and perceived ease of use of paylater services on the financial well-being of Generation Z in DKI Jakarta. This study employed a quantitative approach with a causal associative research design. The sample was selected using purposive sampling, while data were collected through a structured questionnaire using a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that financial literacy has a positive and significant effect on financial well-being, and self-efficacy also has a positive and significant effect on financial well-being. Meanwhile, the perceived ease of use of paylater services has a positive but insignificant effect on financial well-being . These findings suggest that the financial well-being of Generation Z is influenced more by financial management capabilities and confidence in managing personal finances than by the ease of using paylater services. Keywords: financial literacy, self-efficacy, perceived ease of use of paylater, financial well-being, Generation Z.